To solve this system of equations using substitution, we can substitute the expression for y from the first equation into the second equation.
y = 2 + 3x
Substitute y with 2 + 3x in the second equation:
4x - 3(2 + 3x) = -16
4x - 6 - 9x = -16
-5x - 6 = -16
-5x = -10
x = 2
Now that we have found the value of x, we can substitute it back into the first equation to find the value of y:
y = 2 + 3(2)
y = 2 + 6
y = 8
Therefore, the solution to the system of equations is:
(x, y) = (2, 8)
Solve the systems of two equations using substitution.
y = 2 + 3x
4x - 3y = -16
(___, ___)
1 answer